That Reminds Me - Owusu, Derek (Merky Books, 2019)
This is the story of K. K is sent into care before a year marks his birth. He grows up in fields and woods, and is happy, he thinks. When K is eleven, the city reclaims him. He returns to an unknown mother and a part-time father, trading the fields for flats and a community that is alien to him. Slowly he finds friends. Eventually, he finds love. He learns how to navigate the city. But as he grows, he begins to realise that he needs more than the city can provide...
Keywords: Fiction